In vivo Neural Crest Cell Migration Is Controlled by “Mixotaxis” - Barriga, Elias H.; Theveneau, Eric (Frontiers in Physiology, 2020)
Directed cell migration is essential all along an individual’s life, from embryogenesis to tissue repair and cancer metastasis. Thus, due to its biomedical relevance, directed cell migration is currently under intense research. Directed cell migration has been shown to be driven by an assortment of external biasing cues, ranging from gradients of soluble (chemotaxis) to bound (haptotaxis) molecules. Not only molecular gradients have been shown to drive directed cell migration, but also in vitro experiments show that gradients arising from the mechanical properties of the migratory substrate (duro/mechanotaxis) and electric fields (electro/galvanotaxis) as well as iterative biases in the environment topology (ratchetaxis) can do so. Since cells migrating in vivo are exposed to a challenging environment composed of a convolution of biochemical, biophysical and topological cues, it is highly unlikely that cell migration would be guided by an individual type of ‘taxis’. This is especially true since numerous molecular players involved in the cellular response to these biasing cues are often recycled, serving as sensor or transducer of both, biochemical and biophysical signals. In this review, we confront literature on Xenopus cephalic neural crest cells with that of other cell types to discuss the relevance of the current categorization of cell guidance strategies. Furthermore, we emphasize that while studying individual biasing signals is informative, the hard truth is that cells migrate by performing a sort of “mixotaxis”, where they integrate and coordinate multiple inputs through shared molecular effectors to ensure robustness of directed cell motion.